2007
DOI: 10.1097/01.ccm.0000251640.77679.d7
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 is increased in severe sepsis: Correlation with inflammatory mediators

Abstract: First, patients' serum Ang-2 levels are increased during severe sepsis and associated with disease severity. The strong relationship of serum Ang-2 with serum tumor necrosis factor-alpha suggests that the latter may participate in the regulation of Ang-2 production in sepsis. Second, inflammatory mediators reduce Ang-2 release from human lung microvascular endothelial cells, implying that this vascular bed may not be the source of increased Ang-2 in human sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
151
5
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(177 citation statements)
references
References 38 publications
16
151
5
5
Order By: Relevance
“…In agreement with the present results, several studies exhibited a positive correlation between Ang-2 serum levels and the severity of the sepsis [18,21]. A statistically significant association between serum levels of Ang-2 and mortality was not demonstrated in the present study, despite this being reported in other studies [29].…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In agreement with the present results, several studies exhibited a positive correlation between Ang-2 serum levels and the severity of the sepsis [18,21]. A statistically significant association between serum levels of Ang-2 and mortality was not demonstrated in the present study, despite this being reported in other studies [29].…”
Section: Discussioncontrasting
confidence: 42%
“…Increased plasma Ang-2 levels are reported in critically ill patients with sepsis and are associated with increased hospital mortality [17,18,19,20,21], as well as being correlated with the severity of illness [16,22].…”
Section: Introductionmentioning
confidence: 99%
“…In critically ill patients, the release of Ang-2 directly reflects vascular barrier breakdown. Orfanos et al (2007) could demonstrate that Ang-2 serves as marker to discriminate between sepsis and severe sepsis (p < 0.05). The authors investigated serum Ang-2 levels and could also show that Ang-2 acts similar to tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, two very important sepsis markers (p < 0.001).…”
Section: Ang-1 and -2mentioning
confidence: 99%
“…2 While the role of angiopoietin 2 (Ang2) in regulating angiogenesis and vascular integrity has been well recognized, 7,8 recent reports have implicated an important role in inflammation. [9][10][11][12] Ang2 expression is increased dramatically at the sites of endothelial activation and is induced by various cytokines. 13 The release of Ang2 resulted in rapid destabilization of the endothelium and triggered an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%